(untitled) (Research, Society and Development, 2023)
Abstract: Body composition is a factor for evaluating the physical capacity of athletes. High levels of fat mass limit speed and make it difficult to perform movements, compromising the performance of athletes. Objective: To determine the body composition profile of futsal athletes. Methodology: This is a descriptive-analytical longitudinal study. The study population included futsal athletes who participated in the 2022 National Futsal League. The study sample included a total of 186 athletes, making up 48% of the population. Anthropometric measurements of four skinfolds were taken: triceps, subscapular, suprailiac and abdomen, in three different moments during the games. Measurements were performed using a scientific adipometer. The sampling technique adopted was simple random. Analysis of variance was used to analyze repeated measures with Tukey’s post hoc. The significance level adopted was 5% (p ≤ 0.05). Results: There was a significant variation, in the three evaluations carried out, in the total body weight, fat percentage, lean mass and fat weight between the wing position and the other tactical positions (p < 0.001). There was no significant difference in the percentage of fat between the tactical positions in the three evaluations performed. Conclusion: Body composition measurements can be used as a guiding and normative parameter for improving the performance of futsal athletes, between different tactical positions. Conclusion: When comparing tactical positions, significant differences were found in total body weight, lean mass and fat weight.